Problem of the Classification of Quantitative Noun in the German Language - Elvira L. Shubina (Vestnik MGIMO-Universiteta, 2015)
This work is dedicated to the semantic classification of quantitative noun on the basis of a structural study (Nquant + (Adj) +N) (ein Glas frisches Wasser), since this model reveals the greatest variety of grammatical formulation. These word combinations can form by the genitive government eine Tasse starken Kaffees by the grammatical agreement ein Eimer kaltes Wasser, or by the adjunction mit einem Korb reife Apfel. The suggested classification of the noun performing the function of the first components is based on the form of the noun acting as the first component. Types of the first components fall into three groups: 1. The nouns, which specify quantitative characteristics of objects and substances. Two subgroups are also distingshed: word combinations with a noun in a singular form Nquant1a as the second component and word combinations with a noun in a plural form as the second component Nquant1b; 2. The nouns defining a group of living beings and objects Nquant2; 3. The nouns which formation is grounded on quantitative nouns Nquant3. Normative recommendations on the choice of subordinate connection type should be connected at least at the present stage of existence of German literary language, exactly with the semantics of the nouns which are the first components in these word combinations. The article illustrates that all types of constructions (organizes whether on the basis of government, agreement and or adjunction) are connected with the completely specific semantic characteristics of the name, i.e., these nouns belong to one of three groups of noun - first components.